Temporal Transfer of Locomotion Style. Issue 2 (1st April 2015) - Kim, Yejin; Kim, Myunggyu; Neff, Michael
Abstract : Timing plays a key role in expressing the qualitative aspects of a character's motion; that is, conveying emotional state, personality, and character role, all potentially without changing spatial positions. Temporal editing of locomotion style is particularly difficult for a novice animator since observers are not well attuned to the sense of weight and energy displayed through motion timing; and the interface for adjusting timing is far less intuitive to use than that for adjusting pose. In this paper, we propose an editing system that effectively captures the timing variations in an example locomotion set and utilizes them for style transfer from one motion to another via both global and upper‐body timing transfers. The global timing transfer focuses on matching the input motion to the body speed of the selected example motion, while the upper‐body timing transfer propagates the sense of movement flow — succession — through the torso and arms. Our transfer process is based on key times detected from the example set and transferring the relative changes of angle rotation in the upper body joints from a timing source to an input target motion. We demonstrate that our approach is practical in an interactive application such that a set of short locomotion cycles can be applied to generate a longer sequence with continuously varied timings.